2022
DOI: 10.1002/sres.2865
|View full text |Cite
|
Sign up to set email alerts
|

Applications and development of artificial intelligence system from the perspective of system science: A bibliometric review

Abstract: With the rapid development of big data, 6G, Internet of Things (IoT) and other information and communication technologies (ICTs), artificial intelligence (AI) has ushered in new opportunities for more advancements. AI systems are changing the survival and development of human society. This study focuses on the research and application of AI systems within the scientific framework of systems thinking. From scientometrics, this study adopts cocitation analysis and keywords co‐occurrence analysis to sort existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…We also demonstrated that every internal implementation factor is either directly dependant on the IT infrastructure of the organisation or indirectly connected to it through a short causal loop. It is probable therefore that every organisation's attempt to move towards Industry 4.0 stands and falls with their ability to efficiently manage and scale their IT infrastructure, which may further help to explain why a great deal of Industry 4.0 literature is still focused on Industry 4.0 technologies (Ghobakhloo, 2020; Jiang et al, 2022; Nara et al, 2021). However, our findings also show that ‘IT Infrastructure’ has the second highest in‐degree, which is unusual for high out‐degree variables in a network and indicative of a dynamic and complex relationship to other factors.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that every internal implementation factor is either directly dependant on the IT infrastructure of the organisation or indirectly connected to it through a short causal loop. It is probable therefore that every organisation's attempt to move towards Industry 4.0 stands and falls with their ability to efficiently manage and scale their IT infrastructure, which may further help to explain why a great deal of Industry 4.0 literature is still focused on Industry 4.0 technologies (Ghobakhloo, 2020; Jiang et al, 2022; Nara et al, 2021). However, our findings also show that ‘IT Infrastructure’ has the second highest in‐degree, which is unusual for high out‐degree variables in a network and indicative of a dynamic and complex relationship to other factors.…”
Section: Discussionmentioning
confidence: 99%
“…To give context and set the stage for our deeper dives, we'll first explore the historical evolution of spacecraft control systems, drawing attention to the milestones and the challenges that emerged with the advent of nonlinearity in spacecraft dynamics [33]. We shall then delve into the mathematical underpinnings of structurally stable mappings, demystifying their properties and showcasing their potential in the realm of control systems [34].…”
Section: Related Workmentioning
confidence: 99%
“…30 However, existing studies on big data have mainly focused on technical debates, and research on smart technologies and smart supply chain management should improve operational performance. 35 Figure 1 illustrates the conceptual framework of this study.
Figure 1.Conceptual framework.
…”
Section: Literature Reviewmentioning
confidence: 99%